FEATURES OF DIABETES MELLITUS IN HIV-INFECTED PATIENTS - Shagazatova, B.X.; Mirkhaydarova, F.S.; Artikova, D.M.; Axmedova, F.Sh.; Kudratov, N.A. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Diabetes mellitus is one of the urgent problems of contemporary medicine, and today it is growing radiply. In diabetes, the risk of such diseases as lung tube, chronic hepatitis B,C and HIV increases. The increase in the number of HIV-infected patients and the prolonged life expectancy increase the frequency of joint management of these two diseases.